Growth Performance of Crossbred Calves (HF X K) under Different Milk Feeding Methods - Patel, Jigar H; Wadhwani, Kishan N; Trivedi, Manoj M; Lunagariya, Pravin M; Patel, Ashish C (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was conducted to assess performance of crossbred calves on different milk feeding methods. Total 36 crossbred calves were selected and allotted in two treatments, viz., T1: Pail method and T2: Bucket with nipple method. Each treatment had 18 calves for a period of 126 days, in which first 91 days consider as pre-weaning period and 91-126 days as post-weaning period. All the new born calves were immediately separated from their dams and fed fix quantity of milk in a day, half morning, half evening. Afterward, the calves were offered 16, 8 and 4 % BW of milk for the age of 42, 63 and 91 days, respectively, in both milk feeding methods. Concentrate, dry and green fodders were offered ad libitum on first, eighth and forty two days’ of age. There were no treatment differences in body weight, total gain and average daily gain in b. wt. in pre- and post-weaning periods. However, the calves under bucket with nipple method in pre-weaning period gained higher body weight (96.63 ± 3.34 vs. 93.55 ± 3.81 kg), total gain (34.58 ± 1.21 vs. 32.45 ± 1.58 kg) and average daily gain (752.77 ± 34.37 vs. 730.95 ± 36.94 g) as compared to pail milk feeding method. The body measurements of crossbred calves, viz., body length, height at wither and heart girth at initial and final stage were numerically higher in calves under bucket with nipple milk feeding method. The birth weight of calves less than 30 kg grew slower than above 30 kg birth weight throughout the experiment. The male calves had numerically higher body weight than female calves. The study revealed non-significantly improved performance under bucket with nipple method as compared to pail milk feeding and that calves birth weight has influence in their subsequent growth performance also.